Health-related quality of life in children after surgical repair of esophageal atresia: a cross-sectional study in China - Feng, Zhong; Zhu, Haitao; He, Weijing; Peng, Xueni; Gao, Runnan; Tian, Yuxin; Cao, Xuqing; Chen, Gong; Dong, Kuiran; Zheng, Shan; Shen, Chun (Frontiers in Pediatrics, 2024)
Objective: To investigate health-related quality of life (HRQOL) of in postoperative esophageal atresia (EA) patients and identify its potential influencing factors.: A total of 102 EA children who had previously visited our hospital participated in this cross-sectional study. Basic data and disease data of the patients were collected. The HRQOL was measured with Pediatric Quality of Life Inventory TM 4.0 (PedsQL TM 4.0) and EA-QOL questionnaire and ranked on a reverse 0-100 scale, with a higher number indicative of a better HRQOL perception. The scores of PedsQL TM 4.0 in children with EA were collected and compared with demographically matched healthy control group. Meanwhile, the condition-specific HRQOL of EA was analyzed by EA-QOL-questionnaire and potential clinical factors that influenced the HRQOL were determined by generalized linear model. Results: The group of EA and control reached a similar score in the generic PedsQL TM 4.0 (EA group: 89.41±6.54; control: 89.41±6.54; p = 0.670). There was no significant difference between the EA group and the control group in other domains except the school functioning. Condition-specific HRQOL in 2-7-year-old group had highest score in social isolation & stress domain and lowest score in physical health & treatment domain, with an overall quality of life score of 83.48±10.22; Scores of 8-17-year-old group were relatively high in social relationships and health & well-being and lowest in eating domain, with an overall quality of life score of 89.43±8.57. Heart malformation, complicated esophageal surgery history, respiratory symptoms and digestive symptoms in the past 1 month were the main factors affecting HRQOL of children aged 2-7 years. Complicated esophageal surgery history, respiratory symptoms and digestive symptoms in the past 1 month were the main factors affecting the HRQOL of children aged 8-17 years.The findings suggest that patients with EA generally had a good HRQOL. However, EA children with postoperative complications and associated symptoms have lower scores in the EA-QOL questionnaire.